Efektivitas Penerapan Telemental Konseling terhadap Penurunan Kecemasan Remaja Akibat Paparan Informasi Covid 19 di Kota Padang - Windy Freska; Rika Sarfika; Randy Refnandes (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The Coronavirus disease 2019 (COVID-19) epidemic in China is a global health threat, which causes fear, anxiety in receiving the right information according to the mental health needs of society. Teenagers are included in the group who experience the psychological impact of Covid 19 who experience anxiety. Adolescents are more receptive to the use of smartphone applications, health authorities may consider providing psychoeducation and online or smartphone-based psychological interventions. This study aims to determine the effectiveness of implementing Telemental Counseling in Padang city adolescents in 2020. The design used in this study was a Quasi experimental design with a pre and post control group design approach. The sampling technique was Simple Random Sampling with a total sample of 44 people, 22 people in the intervention group and 22 from the control group. This study used the Revised Children's Manifest Anxiety Scale (RCMS) questionnaire. Data analysis was performed using Paired T-Test. The results of this study showed a decrease in the level of anxiety in adolescents in the intervention group, namely the average score of anxiety before being given the application of Telemental counseling in the experimental group was 21.18 and 17.32 afterwards. The results of this statistical test show that there is an effect of providing telemental counseling in the intervention group on reducing anxiety in adolescents in Padang City. The statistical test results obtained p-value = 0.000 (p <0.05).